Mandibular morphometric analysis for sex assessment: A retrospective radiographic study - Raghdaa A Mostafa; Mona Abou El-Fotouh (Wolters Kluwer Medknow Publications, 2020)
Objectives: The purpose of this study was to determine the value of mandibular morphometric measurements in sex assessment using digital panoramic radiographs in a sample of dentate Egyptian patients. Methods: A total of 200 digital panoramic radiographs (i.e.,100 males, 100 females) with age ranges between 20 and 60 years were selected. The samples were divided into 4 age groups with 10 years intervals. Maximum ramus width, minimum ramus width, condylar length, coronoid length, ramus length, gonial angle, ramus notch depth, bigonial width, horizontal length, and diagonal length were measured digitally for each subject. A comparison between different sex groups and age ranges was carried out and the mean values were calculated. Results: Mean results for minimum ramus width, condylar length, coronoid length, and ramus length were statistically significant for gender differences (P < 0.05).The mean of all measurements, except for gonial angle, ramus notch depth, and horizontal length, in males, was higher than that of females. Conclusions: Mandibular morphometric measurements assessed using panoramic radiographs can be used for sex assessment when compared to a known population standard.